Rewilding systemic practice - Santin, Chiara (Murmurations: Journal of Transformative Systemic Practice, 2021)
This paper is written in the context of the current ecological crisis affecting physical and mental health, social, economic, and political contexts, at local and global levels which calls for the disruption of old ways of thinking, living and moving towards the future through collective action. One way of responding as a systemic and family psychotherapist, has been my experience of rewilding my systemic practice with individuals, couples, and families in the UK since taking therapy outdoors. I will offer some examples of ecotherapy as part of my own personal and professional journey in “coming home” through nature, becoming an outdoor designer of therapeutic space and a minimalist wild therapist. I invite us all to re-think and re-create a therapeutic space which, by its very essence, is wild, meaning boundaryless, infinitely spacious and unpredictable. It can open up opportunities for creativity, for using metaphors to explore meanings beyond words. Nature becomes not only the context in which I practice but my co-therapist or even the primary therapist. Together we can enrich the therapeutic process through moments of magic and facilitate change using a wild reflecting team. In my experience of ecotherapy, voices from the wild carry unique messages, for example, birdsong can provide unexpected voices, useful interruptions or disruptions that can enrich the therapeutic process. Such a wild reflecting team can also be a daring metaphor to welcome the unexpected and unfamiliar into our systemic practices and relationships, to include new emerging and marginalised perspectives which may bring us all more in touch with our wildness, lost indigenous ways of relating and shape our futures through collective action.